Does the Importance of Apparel Product Attributes Differ by Country? Testing Kano's Theory of Attractive Quality in Four Countries. (January 2015) - Jin, Byoungho; Bennur, Shubhapriya
Built on Kano's theory of attractive quality, this study posits that apparel attributes contributing to customer satisfaction differ by a country's economic development level since consumers' expectations toward apparel products change. Analyses with data collected in four countries (India, China, Korea, and the U.S.) supported all hypotheses. That is, apparel attributes were classified into different Kano's categories by country. Attributes classified as performance and attractive categories contributed to satisfaction more than the attributes classified in the other categories, regardless of country. Collectively, the findings suggest that as a country's economy advances, the role of brand is diminishing and attributes such as fashionability and versatility become more important in creating customer satisfaction. By discovering the life cycle of each attribute and tracing the path from developing countries to developed countries, this study provides an initial tool to predict how consumers' expectations toward an apparel product shift as a country advances economically.